(untitled) (Politeja, 2025)
RESEARCH ON BLACK CHURCHES’ POLITICAL ACTIVISM IN THE CONTEXT OF POLITICAL SCIENCE OF RELIGION The aim of this article is to analyze the evolution of research on Black churches’ political activism, focusing especially on political scientists’ contributions. The author also investigates how the emergence of the new sub-discipline, known as the political science of religion or politology of religion, influenced the development of political studies on Black churches.